Problems of Financing SMEs in Ghana: A Case Study of the Sunyani Municipality - Prempeh, Kwadwo Boateng (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2015)
Small and medium enterprises play an important role in the development of a country. The growth of SMEs is also important for the world economy which has been widely discussed in recent years. Although the problems SMEs face in accessing finance are well known, still there are some research gaps that need to be filled. The main focus of this research is to explore the nature and the characteristics of SMEs together with the financial constraints facing the SMEs. Basically the research focuses on Sunyani Municipality as the main area of study, but it will also cover the problems of SMEs for the other parts of the world under the same main purpose of this research. The research is a case study. Moreover, the nature of data collected for this project is both quantitative and qualitative. Questionnaires and interviews are the main tools for collecting data. Relevant literature is also reviewed. The Researcher has concluded that many studies have shown most of the SMEs lack access to finance for starting, operating and expanding their businesses, therefore access to finance is always quoted as a major constraint for all SMEs and can seriously affect their ability to survive, upgrade the technology in their business, increase their capacity and even in many cases, expand their market, improve management system or increase productivity as well as profitability. The findings will assist policy makers, development agencies, SME owners and financial institutions to ascertain the appropriate strategy to improve the SME financing.